Environment-friendly fiber textile composite material and environment-friendly production process thereof
By combining natural fibers with recycled polyester fibers and adding functional additives such as flame retardant and antibacterial, optimizing the fiber structure and using environmentally friendly adhesives, the problems of VOC emissions and insufficient functions of existing fiber composite materials during the production process are solved, and the production of high-performance, environmentally friendly fiber composite materials is achieved.
Patent Information
- Application Number
- CN202510017774.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
AI Technical Summary
Existing fiber composites produce volatile organic compounds (VOCs) during the production process, which is potentially harmful to the environment and human health. They lack special functions such as flame retardant and antibacterial, and cannot meet the application needs in special environments.
The combination of natural fibers and recycled polyester fibers is used, and functional additives such as flame retardants, antibacterial agents and self-cleaning coatings are added. The fiber structure is optimized by electrospinning to form a fiber network with porous properties and high surface area. Water-based polyurethane adhesive is used for low-temperature bonding to reduce VOC emissions.
It achieves the environmental protection performance of the material while ensuring high strength and durability, so that the material has excellent hygroscopicity, breathability and biodegradability, ensuring the stability and adhesion effect of the material structure, and at the same time gives the composite material multifunctional properties of fire-proof, flame-resistant, antibacterial and mildew-proof and self-cleaning.
Smart Images

Figure CN119799026A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textile composite materials, in particular to an environmentally friendly fiber textile composite material and an environmentally friendly production process thereof. Background Art
[0002] With the increasing global environmental awareness and the increasing demand for sustainable resource development, the manufacturing and application of traditional fiber composite materials face new challenges. Most fiber composite materials in the existing market use chemical synthetic fibers and organic solvent adhesives. These materials are prone to produce volatile organic compounds (VOCs) during the production process, which are potentially harmful to the environment and human health. At the same time, many fiber materials lack special functions such as flame retardancy and antibacterial properties, and cannot meet the application requirements in special environments. In addition, the material's comfort indicators such as air permeability and hygroscopicity are also difficult to match with sustainability requirements.
[0003] To solve these problems, the present invention proposes an environmentally friendly fiber textile composite material, which realizes an environmentally friendly, durable, multifunctional high-performance composite material by combining natural fibers with recycled polyester fibers and adding functional additives such as flame retardants, antibacterial agents and self-cleaning coatings to meet the market demand for modern environmentally friendly fiber composite materials.
[0004] 1. Patent document CN105818492B discloses a bioactive phosphate-based continuous glass fiber textile composite material and its use. The above patent achieves that the mechanical properties of the bioactive phosphate-based continuous glass fiber textile composite material reach the level of human bones, and the mechanical properties match those of bone tissue. At the same time, it has excellent biocompatibility, degradability and absorbability, which can be comparable to natural bones, and has good processing performance. However, the above patent cannot achieve while ensuring high strength and durability, enhancing the environmental performance of the material, so that the material has excellent hygroscopicity, air permeability and biodegradability.
[0005] 2. Patent document CN108456933B discloses a method for preparing lignin-rich fibers for textiles and composite materials by high-temperature directional degumming. The above patent achieves that the tensile breaking strength of the composite material made of lignin-rich fibers prepared by the present invention is more than 50% higher than that of the composite material made of lignin-rich fibers after conventional alkali degumming, and the bending strength is more than 80% higher. However, the above patent cannot ensure the stability of the material structure and the bonding effect, while reducing the emission of volatile organic compounds.
[0006] 3. Patent document CN104097358B discloses a nanofiber composite material with anti-ultraviolet function and a method for manufacturing the same. The above patent realizes the use of an electrostatic spinning method to cover a textile material with an electrostatic nanofiber film, and fixes the fiber film on the surface of the fabric by chemical or physical means to obtain a high-performance anti-ultraviolet effect and a fabric with good moisture absorption and breathability. However, the above patent cannot achieve the multifunctional properties of giving the composite material fire retardant, antibacterial and mildew-proof, and self-cleaning.
[0007] 4. Patent document CN111621122B discloses a composite material and its preparation method and extrusion equipment. The above patent can solve the problem that materials prepared from waste textiles cannot replace wood-plastic composite materials. However, the above patent cannot achieve the optimization of fiber structure by electrospinning to form a fiber network with porosity and high surface area, thereby improving the air permeability, hygroscopicity and mechanical strength of the material.
[0008] In summary, the above patents cannot achieve the goal of ensuring high strength and durability while enhancing the environmental performance of the material, making the material have excellent hygroscopicity, air permeability and biodegradability, ensuring the stability of the material structure and the bonding effect, while reducing the emission of volatile organic compounds, giving the composite material the multifunctional properties of fire retardancy, antibacterial and mildew resistance, and self-cleaning, and using electrospinning to optimize the fiber structure to form a fiber network with porosity and high surface area, and improving the material's air permeability, hygroscopicity and mechanical strength, resulting in poor material functionality, low strength, poor comfort in use, and high pollution, high energy consumption, and difficulty in degradation during the production process. To this end, the present application proposes an environmentally friendly fiber textile composite material and its environmentally friendly production process that can achieve high strength and durability while enhancing the environmental performance of the material, so that the material has excellent hygroscopicity, air permeability and biodegradability, ensure the stability of the material structure and the bonding effect, and at the same time reduce the emission of volatile organic compounds, give the composite material multifunctional properties of fire retardancy, antibacterial and mildew resistance, and self-cleaning, and use electrospinning to optimize the fiber structure to form a fiber network with porosity and high surface area, thereby improving the material's air permeability, hygroscopicity and mechanical strength. Summary of the invention
[0009] The purpose of the present invention is to provide an environmentally friendly fiber textile composite material and its environmentally friendly production process, so as to solve the problem proposed in the above-mentioned background technology that it is impossible to enhance the environmental performance of the material while ensuring high strength and durability, so that the material has excellent hygroscopicity, air permeability and biodegradability, ensure the stability of the material structure and the bonding effect, and at the same time reduce the emission of volatile organic compounds, give the composite material the multifunctional properties of fire retardancy, antibacterial and mildew resistance, and self-cleaning, and use electrospinning to optimize the fiber structure to form a fiber network with porosity and high surface area, thereby improving the air permeability, hygroscopicity and mechanical strength of the material, resulting in poor material functionality, low strength, poor comfort of use, high pollution, high energy consumption and difficulty in degradation during the production process.
[0010] To achieve the above object, the present invention provides the following technical solutions: an environmentally friendly fiber textile composite material, comprising natural fiber, regenerated fiber, environmentally friendly adhesive and functional additives, wherein the natural fiber is a fiber material derived from renewable resources, and the natural fiber is selected from one or more of bamboo fiber, cotton fiber, flax fiber, hemp fiber and coconut shell fiber, and the natural fiber accounts for 30-60% of the weight of the composite material, the natural fiber has good biodegradability, moisture absorption and air permeability and antibacterial properties, the bamboo fiber has natural antibacterial properties, air permeability and UV resistance, the cotton fiber has moisture absorption and softness, the flax fiber and hemp fiber have tensile strength and wear resistance, and the coconut shell fiber provides corrosion resistance and degradability; The regenerated fiber is a regenerated polyester fiber made by crushing and melt spinning recycled waste textiles / waste plastics, and the regenerated polyester fiber accounts for 30-50% of the weight of the composite material. The regenerated polyester fiber has high mechanical strength and durability, and avoids chemical pollution through physical processing; The environmentally friendly adhesive is a water-based polyurethane / bio-based adhesive, which accounts for 5-10% of the weight of the composite material and is used to efficiently bond the natural fiber to the recycled fiber in a low temperature environment. The adhesive does not release volatile organic compounds (VOC) during the curing process; The functional additive is selected from one or more flame retardants, antibacterial agents and antistatic agents of natural origin, and the functional additive accounts for 1-5% of the weight of the composite material. The flame retardant is selected from natural mineral silicates / phosphates, the antibacterial agent is selected from antibacterial ingredients extracted from plants (tea tree essential oil / silver ion complex), and the antistatic agent is a natural silicone material.
[0011] Preferably, the natural fiber is bamboo fiber, which has natural antibacterial properties, UV resistance and air permeability. The bamboo fiber accounts for 40-50% of the weight of the composite material and is extracted and prepared by physical methods to avoid environmental pollution during chemical extraction. The bamboo fiber is physically steamed and mechanically decomposed to ensure the preservation of the natural antibacterial substance bamboo Kun in the fiber. The antibacterial rate of bamboo fiber is ≥95%, which effectively prevents the growth of common pathogens such as Staphylococcus aureus and Escherichia coli, and still maintains its antibacterial properties after 50 cycles of washing.
[0012] Preferably, the regenerated fiber is a regenerated polyester fiber recycled by a physical and mechanical method, and the recycling process of the regenerated polyester fiber comprises the following steps: (1) Physically crush the waste polyester fiber / plastic into particles with an average particle size of 2-5 mm; (2) Melting and spinning the crushed particles at a melting temperature of 230-260°C to form fiber filaments; (3) subjecting the fiber filaments to low-temperature stretching treatment, the stretching temperature is 80-100°C, the stretching ratio is 2.5-3.5 times, and a regenerated polyester fiber with an average diameter of 5-15 um is obtained; (4) The recycled polyester fiber is subjected to heat setting treatment at a setting temperature of 120-140°C to ensure the dimensional stability and mechanical properties of the fiber.
[0013] Preferably, the environmentally friendly adhesive is a water-based polyurethane adhesive, which achieves bonding through water evaporation, has a curing time of 12-24 hours, and a bonding strength of ≥1.2MPa after curing. At the same time, it has no solvent volatilization, avoiding harmful gas emissions of traditional solvent-based adhesives, and is suitable for the production of environmentally friendly fiber composite materials under low temperature conditions.
[0014] Preferably, the functional additive is a natural silicon-based flame retardant, which is prepared by ultrafine grinding of natural mineral silicate powder, with an average particle size of 0.1-2um, and an added amount of 2-3% by weight of the composite material. The flame retardant mechanism of the silicon-based flame retardant is to release inert gas under high temperature conditions and form a barrier layer, which effectively inhibits fiber combustion, and the flame retardant grade reaches UL94 V-0 standard.
[0015] Preferably, the antibacterial agent is tea tree essential oil extracted from plants, which has a broad-spectrum antibacterial property and has inhibitory effects on fungi, bacteria and viruses. The amount of antibacterial additive added is 1-2% of the weight fraction of the composite material. The antibacterial rate of the composite material treated with the antibacterial additive is ≥99%, and does not affect the air permeability and softness of the composite material.
[0016] Preferably, the composite material further comprises a nano-reinforcement material, which is selected from one or more of nano-cellulose, graphene and carbon nanotubes, and the amount of the nano-reinforcement material added is 0.5-3% by weight of the composite material. Nano-cellulose is prepared by high-pressure homogenization of plant fibers, has a high specific surface area and strength, improves the mechanical strength, tear resistance and durability of the composite material, and does not affect the air permeability and environmental protection of the material.
[0017] Preferably, a coating based on photocatalytic reaction is also introduced on the surface of the composite material, the coating based on photocatalytic reaction contains titanium dioxide nanoparticles, the thickness of the coating based on photocatalytic reaction is 50-200nm, and the added amount of titanium dioxide nanoparticles accounts for 0.1-1% of the total surface cotton base of the composite material. When the surface of the material is exposed to ultraviolet light / visible light, the titanium dioxide nanoparticles undergo a photocatalytic reaction to decompose organic pollutants and bacteria on the surface.
[0018] Preferably, the production process comprises the following steps: S1. Pretreatment: Clean, comb and remove impurities from natural fibers to ensure fiber purity; S2. Fiber mixing: The pretreated natural fiber and the recycled polyester fiber are uniformly mixed according to the weight ratio. The electrostatic spinning process is used in the mixing process to prevent the fiber from being entangled and ensure the uniform distribution of the fibers; S3. Adding environmentally friendly adhesive: adding water-based polyurethane adhesive evenly to the fiber mixture by dipping / spraying, so that the water-based polyurethane adhesive is evenly distributed between the fibers, and is naturally cured at room temperature for 12-24 hours; S4. Addition of functional additives: Add functional additives to the fiber mixture treated with water-based polyurethane adhesive to ensure that the functional additives are evenly distributed in the fiber structure to enhance the specific functionality of the composite material.
[0019] Preferably, the production process further comprises the following steps: S11. Physically crush, melt-spin and low-temperature shape the recycled polyester fiber to ensure the mechanical properties of the fiber; S5. Weaving / knitting the treated fiber mixture on an energy-saving braiding / knitting machine to ensure the structural stability and mechanical strength of the fabric; S6. The formed composite material is treated with a biological enzyme to remove surface impurities, and subjected to a low-temperature heat setting treatment to improve softness and dimensional stability, thereby finally obtaining an environmentally friendly fiber-preventive composite material.
[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention combines natural fibers with recycled polyester fibers to ensure high strength and durability while enhancing the environmental performance of the material, so that the material has excellent hygroscopicity, air permeability and biodegradability, solving the problem that natural fibers in traditional fiber materials have single performance, recycled fibers are not environmentally friendly, and it is difficult to take into account both mechanical properties and ecological sustainability. Through the combination of multiple fibers, the service life of the material is extended and environmental pollution is effectively reduced, which is in line with the trend of green environmental protection; 2. The present invention uses a water-based polyurethane adhesive to bond and mold the fibers, thereby ensuring the stability of the material structure and the bonding effect, while reducing the emission of volatile organic compounds, solving the problem that traditional adhesives are highly volatile, a large amount of harmful gases are generated during the production process, and the production safety and environmental protection are affected. The present invention significantly improves the environmental protection of the production process, improves the working environment, and enhances the overall strength of the material; 3. The present invention endows the composite material with multifunctional properties of fire retardancy, antibacterial and mildew resistance, and self-cleaning through the diversified addition of functional additives, thereby solving the problem that traditional fiber materials have poor performance in fire resistance, antibacterial and self-cleaning properties, improving the applicability of the material in a specific environment, extending its service life, and reducing maintenance costs and safety hazards during use; 4. The present invention optimizes the fiber structure and designs the porosity, and adopts electrospinning to optimize the fiber structure to form a fiber network with porosity and high surface area, thereby improving the air permeability, hygroscopicity and mechanical strength of the material, solving the problems of high density, poor air permeability and reduced comfort of traditional fiber materials, achieving good air permeability and hygroscopicity of the material, increasing the comfort of use, and maintaining relatively high mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of the production process of the composite material of the present invention. DETAILED DESCRIPTION
[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] See also Figure 1, an embodiment provided by the present invention: an environmentally friendly fiber textile composite material, comprising natural fiber, regenerated fiber, environmentally friendly adhesive and functional additive, wherein the natural fiber is a fiber material derived from renewable resources, the natural fiber is selected from bamboo fiber, and the natural fiber accounts for 30-60% of the weight of the composite material, the natural fiber has good biodegradability, moisture absorption and air permeability and antibacterial properties, and the bamboo fiber has natural antibacterial properties, air permeability and UV resistance; The regenerated fiber is a regenerated polyester fiber made by crushing and melt spinning recycled waste textiles / waste plastics, and the regenerated polyester fiber accounts for 30-50% of the weight of the composite material. The regenerated polyester fiber has high mechanical strength and durability, and avoids chemical pollution through physical processing; The environmentally friendly adhesive is a water-based polyurethane, which accounts for 5-10% of the weight of the composite material and is used to efficiently bond the natural fiber and the recycled fiber in a low temperature environment. The adhesive does not release volatile organic compounds (VOC) during the curing process; The functional additive is a natural silicon-based flame retardant, which is prepared by ultra-fine grinding of natural mineral silicate powder, with an average particle size of 0.1-2um, and an addition amount of 2-3% by weight of the composite material. The flame retardant mechanism of the silicon-based flame retardant is to release inert gas under high temperature conditions and form a barrier layer, which effectively inhibits fiber combustion, and the flame retardant grade reaches the UL94 V-0 standard; The production process of environmentally friendly fiber textile composite materials includes the following steps: S1. Pretreatment: Clean, comb and remove impurities from natural fibers to ensure fiber purity; S2. Fiber mixing: The pretreated natural fiber and the recycled polyester fiber are uniformly mixed according to the weight ratio. The electrostatic spinning process is used in the mixing process to prevent the fiber from being entangled and ensure the uniform distribution of the fibers; S3. Adding environmentally friendly adhesive: adding water-based polyurethane adhesive evenly to the fiber mixture by dipping / spraying, so that the water-based polyurethane adhesive is evenly distributed between the fibers, and is naturally cured at room temperature for 12-24 hours; The production process also includes the following steps: S11. Physically crush, melt-spin and low-temperature shape the recycled polyester fiber to ensure the mechanical properties of the fiber; S4, knitting the treated fiber mixture on an energy-saving braiding machine / knitting machine to ensure the structural stability and mechanical strength of the fabric; S5. The formed composite material is treated with a biological enzyme to remove surface impurities, and is subjected to a low-temperature heat setting treatment to improve softness and dimensional stability, thereby finally obtaining an environmentally friendly fiber-preventive composite material; Further, bamboo fiber: accounting for 40% of the total mass of the composite material, extracted by physical cooking and mechanical separation, with a fiber length of 20-30 mm, recycled polyester fiber: accounting for 50% of the total mass of the composite material, recycled from discarded plastic bottles, with a fiber diameter of 10 microns and a tensile strength of 600 MPa, water-based polyurethane adhesive: accounting for 7% of the total mass of the composite material, and the bonding strength after curing reaches 1.5 MPa natural silicon-based flame retardant: accounting for 3% of the total mass of the composite material, with an average particle size of 1.5 microns; after physical cooking to remove impurities, the bamboo fiber is mixed with the recycled polyester fiber according to a mass ratio, and electrospinning is performed to ensure uniform distribution of the fibers; water-based polyurethane adhesive is added to the fiber mixture, and after uniform impregnation, it is placed at room temperature for 24 hours for curing; after curing, the natural silicon-based flame retardant is added to the composite material by impregnation to ensure uniform distribution; finally, the composite material is subjected to low-temperature shaping treatment at a temperature of 110°C and a shaping time of 2 hours, and the performance of the formed composite material is tested, and the test results are shown in Table 1 below.
[0024] See also Figure 1 , an embodiment provided by the present invention: an environmentally friendly fiber textile composite material, comprising natural fiber, regenerated fiber, environmentally friendly adhesive and functional additive, wherein the natural fiber is a fiber material derived from renewable resources, the natural fiber is selected from flax fiber, and the natural fiber accounts for 30-60% of the weight of the composite material, the natural fiber has good biodegradability, moisture absorption and air permeability and antibacterial properties, and the flax fiber has tensile strength and wear resistance; The regenerated fiber is a regenerated polyester fiber made by crushing and melt spinning recycled waste textiles / waste plastics, and the regenerated polyester fiber accounts for 30-50% of the weight of the composite material. The regenerated polyester fiber has high mechanical strength and durability, and avoids chemical pollution through physical processing; The environmentally friendly adhesive is a water-based polyurethane, which accounts for 5-10% of the weight of the composite material and is used to efficiently bond the natural fiber and the recycled fiber in a low temperature environment. The adhesive does not release volatile organic compounds (VOC) during the curing process; The functional additive is selected from antibacterial agents of natural origin, and the functional additive accounts for 1-5% of the weight of the composite material, and the antibacterial agent is selected from antibacterial ingredients extracted from plants (tea tree essential oil / silver ion complex); The natural fiber accounts for 40-50% of the weight of the composite material, and is extracted and prepared by physical methods to avoid environmental pollution during chemical extraction. After physical cooking and mechanical decomposition, the preservation of the natural antibacterial substance bamboo in the fiber is ensured. The antibacterial rate of bamboo fiber is ≥95%, which effectively prevents the growth of common pathogens such as Staphylococcus aureus and Escherichia coli, and maintains its antibacterial properties after 50 cycles of water washing. The regenerated fiber is a regenerated polyester fiber recycled by a physical and mechanical method, and the recycling process of the regenerated polyester fiber includes the following steps: (1) Physically crush the waste polyester fiber / plastic into particles with an average particle size of 2-5 mm; (2) Melting and spinning the crushed particles at a melting temperature of 230-260°C to form fiber filaments; (3) subjecting the fiber filaments to low-temperature stretching treatment, the stretching temperature is 80-100°C, the stretching ratio is 2.5-3.5 times, and a regenerated polyester fiber with an average diameter of 5-15 um is obtained; (4) The recycled polyester fiber is heat-set at a temperature of 120-140°C to ensure the dimensional stability and mechanical properties of the fiber; The environmentally friendly adhesive is a water-based polyurethane adhesive, which achieves bonding through water evaporation, has a curing time of 12-24 hours, and a bonding strength of ≥1.2MPa after curing. It also has no solvent volatilization, thus avoiding the emission of harmful gases of traditional solvent-based adhesives, and is suitable for producing environmentally friendly fiber composite materials under low temperature conditions. The antibacterial agent is tea tree essential oil extracted from plants. Tea tree essential oil has a broad-spectrum antibacterial property and has an inhibitory effect on fungi, bacteria and viruses. The amount of the antibacterial additive added is 1-2% of the weight fraction of the composite material. The antibacterial rate of the composite material treated with the antibacterial additive is ≥99%, and the air permeability and softness of the composite material are not affected. Furthermore, flax fiber: accounting for 35% of the total mass of the composite material, the fiber length is 25-35 mm, recycled polyester fiber: accounting for 55% of the total mass of the composite material, the fiber diameter is 12 microns, water-based polyurethane adhesive: accounting for 6% of the total mass of the composite material, the bonding strength after curing reaches 1.3 MPa, tea tree essential oil antibacterial additive: accounting for 2% of the total mass of the composite material; the flax fiber is washed and physically combed to ensure the purity of the fiber; the recycled polyester fiber is melt-spun and mixed with the flax fiber, and then a water-based polyurethane adhesive is added, and naturally cured at room temperature for 18 hours; tea tree essential oil antibacterial additive is added and evenly distributed on the fiber surface through a spraying process to ensure the permeability of the antibacterial component; finally, a low-temperature setting treatment is performed at a temperature of 100°C and a setting time of 1.5 hours; and the performance of the formed composite material is tested, and the test results are shown in Table 2 below.
[0025] See also Figure 1 , an embodiment provided by the present invention: an environmentally friendly fiber textile composite material, comprising natural fiber, regenerated fiber, environmentally friendly adhesive and functional additive, wherein the natural fiber is a fiber material derived from renewable resources, the natural fiber is selected from hemp fiber, and the natural fiber accounts for 30-60% of the weight of the composite material, the natural fiber has good biodegradability, moisture absorption and air permeability and antibacterial properties, and the hemp fiber has tensile strength and wear resistance; The regenerated fiber is a regenerated polyester fiber made by crushing and melt spinning recycled waste textiles / waste plastics, and the regenerated polyester fiber accounts for 30-50% of the weight of the composite material. The regenerated polyester fiber has high mechanical strength and durability, and avoids chemical pollution through physical processing; The environmentally friendly adhesive is a water-based polyurethane, which accounts for 5-10% of the weight of the composite material and is used to efficiently bond the natural fiber and the recycled fiber in a low temperature environment. The adhesive does not release volatile organic compounds (VOC) during the curing process; The functional additive is selected from antibacterial agents of natural origin, and the functional additive accounts for 1-5% of the weight of the composite material. The antibacterial agent is selected from antibacterial ingredients extracted from plants (tea tree essential oil / silver ion complex); The regenerated fiber is a regenerated polyester fiber recycled by a physical and mechanical method, and the recycling process of the regenerated polyester fiber includes the following steps: (1) Physically crush the waste polyester fiber / plastic into particles with an average particle size of 2-5 mm; (2) Melting and spinning the crushed particles at a melting temperature of 230-260°C to form fiber filaments; (3) subjecting the fiber filaments to low-temperature stretching treatment, the stretching temperature is 80-100°C, the stretching ratio is 2.5-3.5 times, and a regenerated polyester fiber with an average diameter of 5-15 um is obtained; (4) The recycled polyester fiber is heat-set at a temperature of 120-140°C to ensure the dimensional stability and mechanical properties of the fiber; The environmentally friendly adhesive is a water-based polyurethane adhesive, which achieves bonding through water evaporation, has a curing time of 12-24 hours, and a bonding strength of ≥1.2MPa after curing. It also has no solvent volatilization, thus avoiding the emission of harmful gases of traditional solvent-based adhesives, and is suitable for producing environmentally friendly fiber composite materials under low temperature conditions. The composite material further comprises a nano-reinforcement material, which is selected from nano-cellulose. The amount of the nano-reinforcement material added accounts for 0.5-3% of the weight of the composite material. The nano-cellulose is prepared by high-pressure homogenization of plant fibers, has a high specific surface area and strength, improves the mechanical strength, tear resistance and durability of the composite material, and does not affect the air permeability and environmental protection of the material. Furthermore, hemp fiber: accounting for 50% of the total mass of the composite material, with a fiber length of 30-40 mm, recycled polyester fiber: accounting for 45% of the total mass of the composite material, with a fiber diameter of 8 microns, water-based polyurethane adhesive: accounting for 3% of the total mass of the composite material, with a bonding strength of 1.4 MPa, nanocellulose: accounting for 2% of the total mass of the composite material, prepared by homogenizing plant fibers, with an average particle size of 0.5 microns; after physical steaming, the hemp fiber is mechanically decomposed and extracted and mixed with recycled polyester fiber; nanocellulose is added to the fiber mixture, and its uniform distribution is ensured by ultrasonic dispersion technology to increase the mechanical strength of the composite material; a water-based polyurethane adhesive is added to ensure that the adhesive is evenly coated and naturally cured for 24 hours; finally, a low-temperature setting treatment is performed at a temperature of 120°C and a setting time of 2 hours; and the performance of the formed composite material is tested, and the test results are shown in Table 3 below.
[0026] See also Figure 1 , an embodiment provided by the present invention: an environmentally friendly fiber textile composite material, comprising natural fiber, regenerated fiber, environmentally friendly adhesive and functional additive, wherein the natural fiber is a fiber material derived from renewable resources, the natural fiber is selected from coconut shell fiber, and the natural fiber accounts for 30-60% of the weight of the composite material, the natural fiber has good biodegradability, moisture absorption and air permeability and antibacterial properties, and the coconut shell fiber provides corrosion resistance and degradability; The regenerated fiber is a regenerated polyester fiber made by crushing and melt spinning recycled waste textiles / waste plastics, and the regenerated polyester fiber accounts for 30-50% of the weight of the composite material. The regenerated polyester fiber has high mechanical strength and durability, and avoids chemical pollution through physical processing; The environmentally friendly adhesive is a water-based polyurethane, which accounts for 5-10% of the weight of the composite material and is used to efficiently bond the natural fiber and the recycled fiber in a low temperature environment. The adhesive does not release volatile organic compounds (VOC) during the curing process; The regenerated fiber is a regenerated polyester fiber recycled by a physical and mechanical method, and the recycling process of the regenerated polyester fiber includes the following steps: (1) Physically crush the waste polyester fiber / plastic into particles with an average particle size of 2-5 mm; (2) Melting and spinning the crushed particles at a melting temperature of 230-260°C to form fiber filaments; (3) subjecting the fiber filaments to low-temperature stretching treatment, the stretching temperature is 80-100°C, the stretching ratio is 2.5-3.5 times, and a regenerated polyester fiber with an average diameter of 5-15 um is obtained; (4) The recycled polyester fiber is heat-set at a temperature of 120-140°C to ensure the dimensional stability and mechanical properties of the fiber; The environmentally friendly adhesive is a water-based polyurethane adhesive, which achieves bonding through water evaporation, has a curing time of 12-24 hours, and a bonding strength of ≥1.2MPa after curing. It also has no solvent volatilization, thus avoiding the emission of harmful gases of traditional solvent-based adhesives, and is suitable for producing environmentally friendly fiber composite materials under low temperature conditions. A coating based on a photocatalytic reaction is also introduced on the surface of the composite material. The coating based on a photocatalytic reaction contains titanium dioxide nanoparticles. The thickness of the coating based on a photocatalytic reaction is 50-200 nm. The amount of the titanium dioxide nanoparticles added accounts for 0.1-1% of the total surface cotton base of the composite material. When the surface of the material is exposed to ultraviolet light / visible light, the titanium dioxide nanoparticles undergo a photocatalytic reaction to decompose organic pollutants and bacteria on the surface. Further, coconut shell fiber: accounting for 45% of the total weight of the composite material, fiber length is 20-30 mm, recycled polyester fiber: accounting for 50% of the total weight of the composite material, fiber diameter is 10 microns, water-based polyurethane adhesive: accounting for 4% of the total weight of the composite material, titanium dioxide (TiO 2 ) Nanoparticle self-cleaning coating: the coating thickness is 100 nanometers, and the titanium dioxide content accounts for 0.5% of the surface area; coconut shell fiber and recycled polyester fiber are mixed and processed according to a ratio; the titanium dioxide nanoparticle coating is applied to the surface of the composite material by electrostatic spraying and irradiated under ultraviolet light for 5 minutes to activate the photocatalytic function; finally, a heat setting treatment is performed at a temperature of 100°C and a setting time of 1 hour; and the performance of the formed composite material is tested, and the test results are shown in Table 4 below.
[0027] Performance test experimental methods and processes: 1. Tensile strength test: Test standard: GB / T 1040-2006 (Test method for tensile properties of plastics) Test equipment: Electronic universal material testing machine Test process: According to the standard requirements, the prepared composite material was cut into dumbbell-shaped specimens of standard size (150 mm × 25 mm × 2 mm) to ensure uniform thickness and no obvious defects; Adjust the electronic universal testing machine to the initial zero position and calibrate the stretching rate and tension sensor; Clamp both ends of the dumbbell-shaped specimen on the fixture of the testing machine to ensure that the sample remains horizontal and without distortion during the stretching process; Start to load the tensile force at a loading rate of 5 mm / min, and record the elongation and stress of the sample during the stretching process until the sample breaks; The maximum tensile force and the elongation of the sample when it breaks are recorded by the testing machine, and the tensile strength (MPa) is calculated. Tensile strength = maximum tensile force / initial cross-sectional area of the sample.
[0028] 2. Tear strength test Test standard: GB / T 3917.3-2009 (Textile fabric tearing performance test) Test equipment: Pendulum tear strength tester Test process: The composite material was cut into a standard rectangular sample (100 mm × 63 mm) and an initial notch was cut in the center of the sample; Clamp the sample on the clamp of the tear tester, making sure the notch is in the middle of the tearing direction; Release the pendulum and use the impact force of the pendulum to tear the sample. The testing machine automatically records the force required to tear the sample (unit: N) The tear strength is calculated based on the force required to tear, and a larger value indicates that the composite material has better tear resistance when subjected to external forces.
[0029] 3. Flame retardant performance test Test standard: UL94 (plastic material flammability test) Test equipment: flame retardant test box, combustion spray gun Testing process: The composite material was cut into strip specimens of 127 mm × 13 mm × 2 mm; Clamp the sample vertically in the flame retardant test box, ensuring that there is a 10mm flame source below the sample; Use a combustion torch to apply a flame (500°C) to the bottom of the sample for 10 seconds, and record the time it takes for the sample to self-extinguish after the flame is removed. If the sample self-extinguishes in less than 10 seconds, repeat the application of the flame; The flame retardancy level is determined by the self-extinguishing time of the sample and whether or not molten droplets are produced. The UL94 V-0 level requires that the material extinguishes within 10 seconds after the fire source is removed, and no molten droplets are produced.
[0030] 4. Antibacterial performance test Test standard: ASTM E2149-13a (antibacterial performance test of antibacterial materials under dynamic contact conditions) Test equipment: biological safety cabinet, constant temperature shaker, culture medium Testing process: Staphylococcus aureus and Escherichia coli were selected as test strains; The composite material was cut into small pieces of 20 mm × 20 mm, disinfected with alcohol and placed in a sterile environment; The bacterial solution was diluted to a certain concentration (10 6 CFU / mL), and placed the material sample instrument in a culture medium containing 0.03% lecithin, and the culture medium was incubated in a 37°C constant temperature shaker for 1 h; After the incubation, take out the samples, rinse them with a diluent containing sterile saline, take an appropriate amount of the diluent and spread it on the agar medium, and count the colonies after culturing for 24 hours; By comparing the number of bacteria before and after the test, the antibacterial rate of the material is calculated: Antibacterial rate = (number of colonies in the control group - number of colonies in the experimental group) / number of colonies in the control group * 100% The inhibition rate above 99% indicates that the material has significant antibacterial effect.
[0031] 5. Moisture absorption test Test standard: GB / T 9995 (Test method for moisture absorption of textiles) Test equipment: Constant temperature and humidity chamber Test process: The composite material samples were cut into 50 mm × 50 mm pieces and the initial mass (M 0 ); Place the sample in a constant temperature and humidity chamber, set the temperature to 50°C and the relative humidity to 65%. After 24 hours, take out the sample and record its mass (M 1 ); According to the mass change of the sample before and after moisture absorption, calculate the moisture absorption rate: Moisture absorption rate = (M 1 -M 0 ) / M 0 ×100%.
[0032] 6. Air permeability test Test standard: GB / T 5453-1997 (air permeability test of textile fabrics) Test equipment: air permeability tester Testing process: Cut the composite material into a standard size of 100 mm × 100 mm; Fix the sample in the fixture of the air permeability tester and set the pressure difference to 100Pa; Start the equipment, the tester applies a constant pressure through the sample surface and records the air flow rate through the sample (in mm / s); The air permeability of the material is calculated based on the air flow rate through the sample, and a higher value indicates that the material has good air permeability.
[0033] 7. Self-cleaning efficiency test Test standard: Internal standard (self-cleaning performance test based on photocatalytic effect) Test equipment: UV light equipment, stain test solution Testing process: Prepare common stain solutions such as oil and dust, and apply the solutions evenly on the surface of the composite material. After drying, record the state of the contaminated samples; The sample was placed under a UV irradiation device with a light intensity of 200 W / m 2 , the irradiation time is 30 minutes; After the illumination is finished, rinse the sample surface with deionized water, measure the residual pollutants, and record the difference in surface cleanliness before and after self-cleaning; Evaluate self-cleaning efficiency by measuring contaminant removal: Self-cleaning efficiency = (initial pollutant mass - residual pollutant mass) / initial pollutant mass × 100% A removal rate higher than 90% indicates that the material has a good self-cleaning effect.
[0034] The performance test results are as follows: Table 1 Bamboo fiber + recycled polyester fiber + natural silicon-based flame retardant
[0035] Table 2 Flax fiber + recycled polyester fiber + tea tree essential oil antibacterial additive
[0036] Table 3 Hemp fiber + recycled polyester fiber + nanocellulose
[0037] Table 4 Coconut shell fiber + recycled polyester fiber + photocatalytic self-cleaning coating
[0038] Working principle: The core of environmentally friendly fiber textile composite materials lies in the selection and combination of their fiber matrix. By using natural fibers (such as bamboo fiber, flax fiber, hemp fiber) mixed with recycled polyester fiber, it not only achieves a sustainable material source, but also makes full use of the physical properties of each fiber. After the fibers are mixed, water-based polyurethane adhesives are used to fix the fiber structure to ensure the stability and durability of the material. Compared with traditional chemical adhesives, water-based adhesives have low volatility and low toxicity, which not only reduces the emission of harmful substances during the manufacturing process, but also improves the environmental friendliness of the material. In addition, functional additives such as flame retardants, antibacterial additives and photocatalytic coatings further enhance the performance of composite materials. These additives are evenly distributed in the fiber structure and can provide additional functions such as flame retardancy, antibacterial and self-cleaning to meet the needs of different environments and applications; Through advanced processes such as electrospinning, ultrasonic dispersion and heat setting, the fiber structure of the composite material is optimized to ensure the effective fusion of the components. The porous structure of the fiber not only improves the air permeability and hygroscopicity of the material, but also gives it good tensile strength and tear resistance. With the addition of functional additives, the material exhibits excellent flame retardant and antibacterial effects under certain conditions. In particular, the self-cleaning coating can decompose organic pollutants under light conditions by using the photocatalytic effect, further extending the service life of the material and reducing cleaning costs.
[0039] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. An environmentally friendly fiber textile composite material, comprising natural fiber, recycled fiber, environmentally friendly adhesive and functional additive, characterized in that: The natural fiber is a fiber material derived from renewable resources, and the natural fiber is selected from one or more of bamboo fiber, cotton fiber, flax fiber, hemp fiber, and coconut shell fiber, and the natural fiber accounts for 30-60% by weight of the composite material. The natural fiber has good biodegradability, moisture absorption and air permeability, and antibacterial properties. The bamboo fiber has natural antibacterial properties, air permeability, and UV resistance. The cotton fiber has moisture absorption and softness. The flax fiber and hemp fiber have tensile strength and wear resistance. The coconut shell fiber provides corrosion resistance and degradability. The regenerated fiber is a regenerated polyester fiber made by crushing and melt spinning recycled waste textiles / waste plastics, and the regenerated polyester fiber accounts for 30-50% of the weight of the composite material. The regenerated polyester fiber has high mechanical strength and durability, and avoids chemical pollution through physical processing; The environmentally friendly adhesive is a water-based polyurethane / bio-based adhesive, which accounts for 5-10% of the weight of the composite material and is used to efficiently bond the natural fiber to the recycled fiber in a low temperature environment. The adhesive does not release volatile organic compounds (VOC) during the curing process; The functional additive is selected from one or more flame retardants, antibacterial agents and antistatic agents of natural origin, and the functional additive accounts for 1-5% of the weight of the composite material. The flame retardant is selected from natural mineral silicates / phosphates, the antibacterial agent is selected from antibacterial ingredients extracted from plants (tea tree essential oil / silver ion complex), and the antistatic agent is a natural silicone material.
2. The environmentally friendly fiber textile composite material according to claim 1, characterized in that: The natural fiber is bamboo fiber, which has natural antibacterial properties, UV resistance and air permeability. The bamboo fiber accounts for 40-50% of the weight of the composite material and is extracted and prepared by physical methods to avoid environmental pollution during chemical extraction. The bamboo fiber is physically steamed and mechanically decomposed to ensure the preservation of the natural antibacterial substance bamboo Kun in the fiber. The antibacterial rate of bamboo fiber is ≥95%, which effectively prevents the growth of common pathogens such as Staphylococcus aureus and Escherichia coli, and still maintains its antibacterial properties after 50 cycles of washing.
3. The environmentally friendly fiber textile composite material according to claim 1, characterized in that: The regenerated fiber is a regenerated polyester fiber recycled by a physical and mechanical method, and the recycling process of the regenerated polyester fiber includes the following steps: (1) Physically crush the waste polyester fiber / plastic into particles with an average particle size of 2-5 mm; (2) Melting and spinning the crushed particles at a melting temperature of 230-260°C to form fiber filaments; (3) subjecting the fiber filaments to low-temperature stretching treatment, the stretching temperature is 80-100°C, the stretching ratio is 2.5-3.5 times, and a regenerated polyester fiber with an average diameter of 5-15 um is obtained; (4) The recycled polyester fiber is subjected to heat setting treatment at a setting temperature of 120-140°C to ensure the dimensional stability and mechanical properties of the fiber.
4. The environmentally friendly fiber textile composite material according to claim 1, characterized in that: The environmentally friendly adhesive is a water-based polyurethane adhesive, which achieves bonding through water evaporation, has a curing time of 12-24 hours, and a bonding strength of ≥1.2MPa after curing. At the same time, there is no solvent volatilization, avoiding the harmful gas emissions of traditional solvent-based adhesives, and is suitable for the production of environmentally friendly fiber composite materials under low temperature conditions.
5. The environmentally friendly fiber textile composite material according to claim 1, characterized in that: The functional additive is a natural silicon-based flame retardant, which is prepared by ultra-fine grinding of natural mineral silicate powder, with an average particle size of 0.1-2um, and an added amount of 2-3% by weight of the composite material. The flame retardant mechanism of the silicon-based flame retardant is to release inert gas under high temperature conditions and form a barrier layer, which effectively inhibits fiber combustion, and the flame retardant grade reaches the UL94 V-0 standard.
6. The environmentally friendly fiber textile composite material according to claim 1, characterized in that: The antibacterial agent is tea tree essential oil extracted from plants. Tea tree essential oil has a broad-spectrum antibacterial property and has inhibitory effects on fungi, bacteria and viruses. The amount of antibacterial additive added is 1-2% of the weight fraction of the composite material. The antibacterial rate of the composite material treated with the antibacterial additive is ≥99%, and it does not affect the air permeability and softness of the composite material.
7. The environmentally friendly fiber textile composite material according to claim 1, characterized in that: The composite material also contains nano-reinforcement materials, which are selected from one or more of nano-cellulose, graphene and carbon nanotubes. The added amount of the nano-reinforcement materials accounts for 0.5-3% of the weight of the composite material. The nano-cellulose is prepared by high-pressure homogenization of plant fibers, has a high specific surface area and strength, improves the mechanical strength, tear resistance and durability of the composite material, and does not affect the air permeability and environmental protection of the material.
8. The environmentally friendly fiber textile composite material according to claim 1, characterized in that: A coating based on a photocatalytic reaction is also introduced on the surface of the composite material. The coating based on a photocatalytic reaction contains titanium dioxide nanoparticles. The thickness of the coating based on a photocatalytic reaction is 50-200 nm. The added amount of the titanium dioxide nanoparticles accounts for 0.1-1% of the total surface cotton base of the composite material. When the surface of the material is exposed to ultraviolet light / visible light, the titanium dioxide nanoparticles undergo a photocatalytic reaction to decompose organic pollutants and bacteria on the surface.
9. An environmentally friendly production process of an environmentally friendly fiber textile composite material, applicable to an environmentally friendly fiber textile composite material and its environmentally friendly production process as claimed in any one of claims 1 to 8, characterized in that: The production process comprises the following steps: S1. Pretreatment: Clean, comb and remove impurities from natural fibers to ensure fiber purity; S2. Fiber mixing: The pretreated natural fiber and the recycled polyester fiber are uniformly mixed according to the weight ratio. The electrostatic spinning process is used in the mixing process to prevent the fiber from being entangled and ensure the uniform distribution of the fibers; S3. Adding environmentally friendly adhesive: adding water-based polyurethane adhesive evenly to the fiber mixture by dipping / spraying, so that the water-based polyurethane adhesive is evenly distributed between the fibers, and is naturally cured at room temperature for 12-24 hours; S4. Addition of functional additives: Add functional additives to the fiber mixture treated with water-based polyurethane adhesive to ensure that the functional additives are evenly distributed in the fiber structure to enhance the specific functionality of the composite material.
10. The environmentally friendly production process of an environmentally friendly fiber textile composite material according to claim 9, characterized in that: The production process also includes the following steps: S11. Physically crush, melt-spin and low-temperature shape the recycled polyester fiber to ensure the mechanical properties of the fiber; S5. Weaving / knitting the treated fiber mixture on an energy-saving braiding / knitting machine to ensure the structural stability and mechanical strength of the fabric; S6. The formed composite material is treated with a biological enzyme to remove surface impurities, and subjected to a low-temperature heat setting treatment to improve softness and dimensional stability, thereby finally obtaining an environmentally friendly fiber-preventive composite material.
Citation Information
Patent Citations
A nanofiber composite material with anti-ultraviolet function and its manufacturing method
CN104097358B
A bioactive phosphate-based continuous glass fiber textile composite material and its applications
CN105818492B
A method for preparing lignin-rich fibers for textiles and composite materials by high-temperature directional degumming
CN108456933B
A composite material and its preparation method and extrusion equipment
CN111621122B
Textile material with waterproof and antibacterial ability and preparation method thereof
CN108286083A
Cited By
Bamboo fiber composite weaving method for environment-friendly bamboo weaving craft product
CN121200166A
Environment-friendly textile composite material and production process thereof
CN121319580A